BRICS+: a Wake-Up Call for the G7? - Katrin Kamin; Rolf J. Langhammer (Cuadernos Económicos de ICE, 2024)
The paper explores whether the changing dynamics of the BRICS potentially influence the formation of economic and political blocs and investigates whether BRICS+ can serve as a geoeconomic counterweight to the G7. Evaluating the impact of resource endowment, trade relations, political regimes, and financial market roles of BRICS+ members on the global economic and political landscapes, the article discusses the geopolitical importance of BRICS+, and the G7 responses. We conclude that the BRICS+ serve as a wake-up call for the G7, urging a reassessment of political and economic ties in the face of a changing global scenario.
Keywords: F1; F3; F5; 330; BRICS; trade; financial markets; resources; geopolitics; G7